Extended electrochemical windows made accessible by room temperature ionic liquid/organic solvent electrolyte systems. - Buzzeo, M; Hardacre, C; Compton, R (2006)
The electrochemical windows of acetonitrile solutions doped with 0.1 M concentrations of several ionic liquids were examined by cyclic voltammetry at gold and platinum microelectrodes. These results were compared with those observed in the commonly used 0.1 M tetrabutylammonium perchlorate/acetonitrile system as well as with neat ionic liquids. The use of a trifluorotris(pentafluoroethyl)phosphate-based ionic liquid, specifically, as supporting electrolyte in acetonitrile solutions affords a wider anodic window, which is attributed to the high stability of the anionic component of these intrinsically conductive and thermally robust compounds.